Saproxylic rove beetles of the subfamily Aleocharinae (Coleoptera, Staphylinidae) in primeval fir forest of the Carpathian National Nature Park - Motruk, Yuriy; Glotov, Sergiy (ScienceRise: Biological Science, 2025)
Saproxylic beetles are insects that depend on dead and decaying wood for at least part of their lifecycle, and play an important ecological roles in European habitats. Together with fungi, they contribute to the destruction of deadwood as well as are involved in decomposition processes and the recycling of nutrients in natural ecosystems. The subfamily Aleocharinae is one of the largest subfamilies of rove beetles. The aim of the study is to investigate the diversity of saproxylic beetles (Coleoptera, Staphylinidae) in primeval fir forest of the Carpathian National Nature Park. Materials and methods. The report is based on the results of observations and collections, which were conducted in coniferous forests of the Carpathian National Nature Park in 2023–2024. All traps were set up and operated yearly during the vegetation season from early April to late September. Results. The fauna of rove beetles of the subfamily Aleocharinae accounts for 44 species, of which 23 species are obligate or facultative saproxylic. The community of rove beetles of the subfamily Aleocharinae, collected in primeval fir forest of the Carpathian National Nature Park, is characterized by a high level of faunal diversity. Conclusions. The community of rove beetles of the subfamily Aleocharinae, collected in primeval fir forest of the Carpathian National Nature Park, is characterized by a high level of faunal diversity. The fauna of rove beetles of the subfamily Aleocharinae accounts for 44 species, of which 23 species are saproxylic. The result of our research is a section of the composition of the beetle community at a certain stage of forest succession. In the future, these data can be used by researchers to assess other territories, in particular with the aim of forming proposals for rational sustainable permanent forest use, which Ukrainian forestry is gradually moving towards